Investigation of electron beam transport in a magnetron gun with a secondary-emission cathode - Dovbnya, A.N.; Zakutin, V.V.; Reshetnyak, N.G. (Вопросы атомной науки и техники, 2006)
Results are reported from the studies of electron beam generation in the magnetron gun and beam transport over distances of 3 and 40 mm. The studies have demonstrated that the beam current and the beam dimensions remain unchanged with the beam transport over a distance of 40 mm from the gun in the increasing magnetic field, the latter being 10 to 15% higher at the Faraday cup than at the cathode.